The role of chlorine atom on the binding between acrylonitrile derivatives and fat mass and obesity‐associated protein. Issue 4 (9th November 2020) - Bai, Ning; Gan, Ya; Li, Xitong; Gao, Shuting; Yu, Wenquan; Wang, Ruiyong; Chang, Junbiao
Abstract: In this work, seven acrylonitrile derivatives were selected as potential inhibitors of fat and obesity‐related proteins (FTO) by the aid of fluorescence spectroscopy, ultraviolet visible spectroscopy, molecular docking, and cytotoxicity methods. Results show that the interaction between 3‐amino‐2‐(4‐chlorophenyl)‐3‐phenylacrylonitrile (1a ) and FTO was the strongest among these derivatives. Thermodynamic analysis and molecular modeling show that the main force between 1a and FTO is hydrophobic interaction. The cytotoxicity test showed that the IC50 value of 1a was 46.64 μmol/L, which indicated 1a had the smallest IC50 value and had the best inhibitory effect on the proliferation of leukemia K562 cells among the seven derivatives. Both our previous results and this work show that chlorine atoms play important role in the binding of small molecules and FTO. This work brings new information for the study of FTO inhibitors.